“Juggling while running”: Emergency remote teaching of translation in times of educational disruption - Stanojević, Mateusz-Milan; Pavlović, Nataša (Meta, 2022)
The COVID-19 pandemic caused an unprecedented educational disruption in university programs worldwide, with translator education being no exception. The sudden and unplanned transition from campus or blended to online instructional environments, termed “emergency remote teaching” or ERT (Hodges, Moore, et al. 2020), imposed a unique strain on students, teachers and institutions. Aiming to reassess the concept of ERT so as to enable a better response in the future, this study investigates the reflections of nine translation teachers from three universities in Croatia on their ERT experience in the March-June semester of 2020. To this end, three semi-structured focus groups were conducted in July 2020. Results show that the teachers had to adapt to the new learning environment and cater to their students’ changed learning and emotional needs, while reorganising their home life and learning new skills. In these circumstances, described by one of the participants as “juggling while running,” the social support given and received by teachers was found to be a crucial factor at play. The experience is shown to have had an impact not only on their ERT, but also on their future practices. Some recommendations are drawn in the conclusion.